Analysis of Transformer Using Flyback Converter Circuit - Ahmad Syarip Hidayatulloh; Rizki Idul Fitriansyah; Sandi Apriliyanto; Bayu; Ahmad Tubagus Zatin; Achmad Choirul Anwar; Andre Ramadhan; Alvin Mei Arisandi; Adi Mulyadi (Fakultas Teknik Universitas PGRI Banyuwangi, 2023)
This paper discusses two types of transformers 3 A and 5 A with the addition of a flyback converter circuit. The transformer 3 A is only able to lower the DC output voltage and cannot produce an AC output voltage. So that the addition of a flyback converter circuit is proposed to change the AC output voltage and increase the voltage based on the desired load. The results of the 3 A transformer test obtained an increased output voltage from 12.21 Vdc to 18.04 Vdc with a constant time period of 1 minute. While testing the 5 A transformer shows that the increase in output voltage is obtained by adding a flyback converter circuit. The result of the output voltage with the addition of a flyback converter circuit reaches 221 Vac to 252.2 Vac. The increase in output voltage is directly proportional to a constant time period of one minute.